Time-on-task effects on human pupillary and saccadic metrics after theta burst transcranial magnetic stimulation over the frontal eye field - Wang, Chin An (2023)
Pupil size undergoes constant changes primarily influenced by ambient luminance. These changes are referred to as the pupillary light reflex (PLR), where the pupil transiently constricts in response to light. PLR kinematics provides valuable insights into autonomic nervous system function and have significant clinical applications. Recent research indicates that attention plays a role in modulating the PLR, and the circuit involving the frontal eye field (FEF) and superior colliculus is causally involved in controlling this pupillary modulation. However, there is limited research exploring the role of the human FEF in these pupillary responses, and its impact on PLR metrics remains unexplored. Additionally, although the protocol of continuous theta-burst stimulation (cTBS) is well-established, the period of disruption after cTBS is yet to be examined in pupillary responses. Our study aimed to investigate the effects of FEF cTBS on pupillary and saccadic metrics in relation to time spent performing a task (referred to as time-on-task). We presented a bright stimulus to induce the PLR in visual- and memory-delay saccade tasks following cTBS over the right FEF or vertex. FEF cTBS, compared to vertex cTBS, resulted in decreased baseline pupil size, peak constriction velocities, and amplitude. Furthermore, the time-on-task effects on baseline pupil size, peak amplitude, and peak time differed between the two stimulation conditions. In contrast, the time-on-task effects on saccadic metrics were less pronounced between the two conditions. In summary, our study provides the first evidence that FEF cTBS affects human PLR metrics and that these effects are modulated by time-on-task.